Abnormal umbilical artery Doppler velocimetry and placental histopathological correlation in fetal growth restriction - R Agarwal; A Tiwari; N Wadhwa; G Radhakrishnan; S Bhatt; P Batra (South African Medical Association, 2017)
Background. Doppler velocimetry (DV) is widely used to assess the vascular formation of the placenta in fetal growth restriction (FGR) and to estimate the haemodynamic condition of the growth-restricted fetus. Umbilical artery (UA) flow is essentially placental, rather than fetal. Hence, DV provides information about the fetal side of the placenta and, alongside placental histopathology, it could possibly help to decipher aetiopathogenesis in FGR cases.Objective. To correlate UA DV findings occurring in FGR with placental findings.Methods. The study was prospective and conducted in a low-income setting. A total of 130 non-anomalous singleton FGR pregnancies (â‰¥24 weeks) were included in the study. All pregnancies were confirmed to be small for gestational age (SGA) after the birth of the neonate. The placental lesions and neonatal outcomes were correlated with DV findings before delivery: 65 cases with normal DV results constituted group 1, and group 2 had 65 cases with abnormal DV results such as reduced flow, absent UA end diastolic flow or reversal of UA end diastolic flow.Results. Group 2 had significantly lower mean (standard deviation) birth weights of 1.59 (0.4) kg v. 1.87 (0.23) kg for group 1 (p<0.001). Considerably higher NICU mortality was seen in group 2 (30.5%) compared with group 1 (6.7%) (p<0.001). The group 2 placentas weighed less, had a higher number of maternal underperfusion (MUP) lesions, higher levels of calcification. Among lesions of MUP, 4 lesions i.e. villous infarction (p<0.001), villous agglutination (p<0.001), syncytial knots (p=0.003) and intervillous fibrin deposition (p=0.001) were present in significantly higher numbers in the abnormal Doppler group compared with the normal Doppler group. Abnormal Doppler had a sensitivity of 80% and specificity of 92.3% for abnormal placental pathology (placental lesions â‰¥3).Conclusions. There was a significantly higher number of MUP lesions and neonatal morbidity in SGA patients with abnormal DV findingsÂ